Meanings of education in the life narratives of educated unemployed women in Pakistan - Khan, Sana (My University, 2024)
In this thesis, I explored the narratives of six educated unemployed women living in the main cities of Pakistan, primarily focusing on their past educational experiences and its meaning in their current unemployed lives. The term "educated unemployed" highlights the contradiction these women face after getting education and being unable to secure employment. Moreover, this study not only addresses the contradiction but also examines the positive outcomes their education has brought into their lives. The findings of this study are based on existing literature on "gender, education, and employment," as well as feminist discussions on women's right to education and work. Central to this research is the focus on the voices and experiences of Pakistani women. This research is based on narrative interviews and thematic analysis, through which various themes emerged. The findings show that although these women’s education did not lead to employment for several reasons, they still experienced positive changes in their lives. However, they also felt that their education is being wasted without corresponding employment opportunities.
Keywords: education, employment, feminist discussions, unemployed women, experiences, Pakistan, Pakistani women, narratives